2023
DOI: 10.3389/fimmu.2023.1101854
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis reveals shared gene signatures and molecular mechanisms between obesity and periodontitis

Abstract: BackgroundBoth obesity (OB) and periodontitis (PD) are chronic non-communicable diseases, and numerous epidemiological studies have demonstrated the association between these two diseases. However, the molecular mechanisms that could explain the association between OB and PD are largely unclear. This study aims to investigate the common gene signatures and biological pathways in OB and PD through bioinformatics analysis of publicly available transcriptome datasets.MethodsThe RNA expression profile datasets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Yang et al explored the relationship between MitoEVs and the immune microenvironment in periodontitis by using machine learning and bioinformatics methods ( Yang et al, 2024 ). Cai et al found a common pattern of gene expression between obesity and periodontitis by analyzing transcriptomic data and identified five important biomarkers ( Cai et al, 2023 ). Huang et al used machine learning combined with L1 regularisation and the LIME model interpreter to identify genes associated with periodontitis ( Huang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al explored the relationship between MitoEVs and the immune microenvironment in periodontitis by using machine learning and bioinformatics methods ( Yang et al, 2024 ). Cai et al found a common pattern of gene expression between obesity and periodontitis by analyzing transcriptomic data and identified five important biomarkers ( Cai et al, 2023 ). Huang et al used machine learning combined with L1 regularisation and the LIME model interpreter to identify genes associated with periodontitis ( Huang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…While P2RY13 is particularly sensitive to ADP, it can be triggered by both ADP and ATP. Research indicates a crucial function of P2RY13 in inflammation and immune imbalance 15 . Several studies have reported that P2RY13 is a key regulator of cholesterol transport and hepatic HDL endocytosis and is involved in bone formation, remodeling, cell survival, and neuroprotection 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al explored the relationship between MitoEVs and the immune microenvironment in periodontitis by using machine learning and bioinformatics methods (Yang et al, 2024). Cai et al found a common pattern of gene expression between obesity and periodontitis by analyzing transcriptomic data and identified five important biomarkers (Cai et al, 2023). Huang et al used machine learning combined with L1 regularisation and the LIME model interpreter to identify genes associated with periodontitis (Huang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%